Identification and Evolution of a Natural Tetr Protein Based on Molecular Docking and Development of a Fluorescence Polari-Zation Assay for Multi-Detection of 10 Tetracyclines in Milk - Wanqiu Xia; Jing Liu; Jianping Wang (Foods, 2022)
In this study, the identity of our recently produced natural TetR protein was identified by using the LC-ESI-MS/MS technique, and its recognition mechanisms, including the binding pocket, contact amino acids, intermolecular forces, binding sites, binding energies, and affinities for 10 tetracycline drugs were studied. Then, it was evolved by site-mutagenesis of an amino acid to produce a mutant, and a fluorescence polarization assay was developed to detect the 10 drugs in milk. The sensitivities for the 10 drugs were improved with IC50 values decreasing from 30.8–80.1 ng/mL to 15.5–55.2 ng/mL, and the limits of detection were in the range of 0.4–1.5 ng/mL. Furthermore, it was found that the binding affinity for a drug was the critical factor determining its sensitivity, and the binding energy showed little influence. This is the first study reporting the recognition mechanisms of a natural TetR protein for tetracyclines and the development of a fluorescence polarization assay for the detection of tetracyclines residues in food samples.